Non-Specified Interstitial Pneumonia (nsip) And Thromboembolic Disease As First Manifestation Of Disease In Primary Sjogren Syndrome: Case Report (2016)
Primary Sjögren Syndrome (pSS) is a chronic inflammatory disease with lymphocytic infiltration and a decrease in function of wxocrine glands, especially lacrimal and saliva glands. The lung involvement includes mucosal dryness; lung interstitial disease (LID) in 10-20% of the cases, non.Hodgkin lymphoma, pleural effusion and rarely Thromboembolic Disease (TD) with pulmonary hypertension, but these almost never precedes the syndrome diagnosis. Objective: To describe a case report of pSS that presents Non-specified Interstitial Pneumonia (NSIP) and TD in Fundacion Valle del Lili.